IMPLEMENTASI KEBIJAKAN PENETAPAN JALUR PENGELUARAN BARANG IMPOR PADA KANTOR PELAYANAN UTAMA BEA CUKAI TIPE C SOEKARNO HATTA TAHUN 2016 - Johan Pramudyo; Pebriana Arimbhi (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
Implementation of Risk management by the Directorate General of Customs and Excise in the form of inspection by risk-based selectivity is still running not yet optimally. It seen still looks much infraction on the green chanel and hit rate on the red line that is still below the standard. This study aims to know and analizing implementation of channel appointment at the At Soekarno Hatta Prime Customs and Excise Office Type C in 2016, to determine the obstacles of those policy implementation and efforts made in overcoming it. This research uses research method with qualitative approach. The results of the research show the policy are well implemented but still inaccurate. Emerging constraints: lack of human resources, updating of importer profiles that have not been optimal and coordination that has not been maximized